Comparative Transcriptome Analysis of Eggplant (Solanum melongena L.) Peels with Different Glossiness - Hong Wang; Zhixing Nie; Tonglin Wang; Shuhuan Yang; Jirong Zheng (Agronomy)
Peel glossiness is an important commercial trait of eggplant (Solanum melongena L.). In this study, two eggplant-inbred lines with different levels of peel glossiness were used to identify genes related to peel glossiness. Paraffin section analysis showed that increased wax thickness and wrinkles on the wax surface of eggplant peels decreased glossiness. Differential gene expression related to eggplant peel glossiness was analyzed by comparing the transcriptomes of eggplant peels with different gloss levels and at different developmental stages. The results identified 996 differentially expressed genes (DEGs), including 502 upregulated and 494 downregulated genes, possibly related to eggplant peel glossiness. GO enrichment and KEGG enrichment analyses revealed that the DNA replication pathway (GO:0003688, GO:0006270) and the photosynthesis pathway (map00195) were downregulated and thus may be associated with reduced eggplant peel glossiness. Expression level analysis of eggplant peels with different glossiness levels revealed that a C2H2 transcription factor gene, two ERF transcription factor genes, one long-chain acyl-CoA synthetase gene, and four wax- or cutin-related genes may be associated with the glossiness of eggplant fruit peels. These findings will help guide future genetic improvements in eggplant peel glossiness.